Two-dimensional hybrid nanosheets of few layered MoSe2 on reduced graphene oxide as anodes for long-cycle-life lithium-ion batteries. Issue 40 (26th September 2016) - Luo, Zhigao; Zhou, Jiang; Wang, Lirong; Fang, Guozhao; Pan, Anqiang; Liang, Shuquan
Abstract : We report the synthesis of a novel 2D hybrid nanosheet constructed by few layered MoSe2 grown on reduced graphene oxide (rGO), which exhibits excellent electrochemical performance as anodes for lithium ion batteries. Abstract : A rational design of two-dimensional (2D) hybrid materials between transition metal dichalcogenides (TMDs) and graphene has received great attention because of their promising applications in the energy field. Herein, we report the synthesis of novel 2D hybrid nanosheets constructed by few layered MoSe2 grown on reduced graphene oxide (rGO). As a proof-of-concept application, the 2D MoSe2 /rGO nanosheets exhibit excellent electrochemical performance as anodes for lithium ion batteries, demonstrating outstanding cycling stability (up to 1000 cycles), and high-rate capability.